Una nueva especie de megaterino (Xenarthra, Megatheriidae) del Mioceno Tardío-Plioceno de Catamarca, Argentina (Ameghiniana, 2014)
A new species of Megatheriinae of the genus Pyramiodontherium is described. This genus was so far represented by a single species, Pyramiodontherilum bergi (Moreno and Mercerat), from the Mio-Pliocene of Catarnarca and Tucumán. The new material was found in levels informally narned "Araucanense" from the Bajo de Andalhualá, Catamarca province (Late Miocene-Pliocene). The rostrum is wider than long, oval in cross section and directed downward; the oblique longitudinal crest frorn the maxillar apophysis of the zygomatic arch up to the base of the rostral portion is marked; the maxillar root of the zygomatic apophysis is high; the upper molariforms are quadrangular in section, the first molariforrn is trapezoidal and the last one, the smallest, is subrectangular with rounded angles and the posterior margin of cornpact dentine forming a concave crest backwards; the prism of the first lower molariforn is more curved than in P. bergi and the preserved portion of the symphysis not so deep; the proxima l diaphysis of the hurnerus is trapezoidal in cross section; the diaphysis of the fernur has lower degree of torsion. Only two monospecific genera of Megatheriinae were known up to date in the Upper Miocene-Pliocene of northwestern Argentina, Plesiomegatherium hansmeyeri Roth and Pyramiodontherium bergi. The nevv species here described, enlarges the diversity both of the megatherines from the "Araucanense" and of the genus.